2009
DOI: 10.5194/aab-52-637-2009
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability and quality of raw Saanen and Alpine goats milk

Abstract: The milk composition and concentration of thiobarbituric acid reactive substances (TBARS) and superoxide dismutase (SOD) activity in fresh and refrigerated raw goat milk of Saanen and Alpine breed at the breeding period were investigated. Low average milk fat, SNF and lactose content were determined in both breeds with no significant differences between breeds regarding the milk yield and milk composition. The significantly higher somatic cell count (SCC) was detected in Saanen goats. The SOD activity and TBAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…59 However, in this review we provided evidence that formation of oxidatively modied products in milk could also result from the formation of NO 2 c during udder inammation, and thus it is more likely an explanation for the formation of rancid avor in large volumes of bulk milk. This conclusion is based on research carried out mainly in one laboratory, but it is substantiated by certain publications: the study of Marenjak et al 60 showed that low-quality milk (i.e., with high somatic cell count) contains more Lpx than high-quality milk and in the study of Mannello et al 61 it was found that nipple-aspirated uid collected from breast cancer women contains increased content of carbonyls on proteins, which suggests that oxidative stress in the mammary gland is involved in the etiology of the disease. The study of Bhat et al 62 sustains our ndings 21 that the content of Lpx and carbonyls may increase during milk storage.…”
Section: Association Between Noc Rsno and No-derived Reactive Speciesmentioning
confidence: 93%
“…59 However, in this review we provided evidence that formation of oxidatively modied products in milk could also result from the formation of NO 2 c during udder inammation, and thus it is more likely an explanation for the formation of rancid avor in large volumes of bulk milk. This conclusion is based on research carried out mainly in one laboratory, but it is substantiated by certain publications: the study of Marenjak et al 60 showed that low-quality milk (i.e., with high somatic cell count) contains more Lpx than high-quality milk and in the study of Mannello et al 61 it was found that nipple-aspirated uid collected from breast cancer women contains increased content of carbonyls on proteins, which suggests that oxidative stress in the mammary gland is involved in the etiology of the disease. The study of Bhat et al 62 sustains our ndings 21 that the content of Lpx and carbonyls may increase during milk storage.…”
Section: Association Between Noc Rsno and No-derived Reactive Speciesmentioning
confidence: 93%
“…Kiyosawa et al (2014) have reported that the SOD activity in milk during storage in the refrigerator (at <5 C) decreased rapidly with storage time and fell to 40% of that of fresh skim milk after 5 days. And, it is also reported that the SOD activity were significantly higher 14 h after the collection and cold storage in both breeds of dairy goats with no difference between the breeds (Marenjak et al 2009). In the milk kept in the freezer (À80 C) for 10 days, the SOD activity did not change in comparison with that of fresh skim milk (Nagasawa et al 1972).…”
Section: The Effect Of Temperature On Sod Activity In Goat Milkmentioning
confidence: 83%
“…MU concentration is influenced by numerous environmental factors such as stage of lactation, parity, season, productivity, and milking time (Schepers and Meijer, 1998;Giaccone et al, 2007;Abdouli et al, 2008), but the most important factors affecting urea formation remain the amount of crude protein intake from the diet and the ratio of crude protein intake to energy, as well as the ratio of degradable and non-degradable proteins in the rumen (Marenjak et al, 2004;Bonanno et al, 2008).…”
Section: Introductionmentioning
confidence: 99%